Impaired thrombin generation and fibrin clot formation in patients with dilutional coagulopathy during major surgery - Schols, Saskia E. M.; Lancé, Marcus D.; Feijge, Marion A. H.; Damoiseaux, Jan; Marcus, Marco A.; Hamulyák, Karly; Cate, Hugo ten; Heemskerk, Johan W. M.; van Pampus, Elisabeth C. M. (Thrombosis and Haemostasis, 2010)
Patients subjected to haemodilution during surgery are at increased risk of bleeding. We hypothesised that, in the acquired dilutional coagulopathy, insufficient haemostasis is due to either insufficient thrombin generation or insufficient fibrin clot formation. In tissue factor-activated plasmas from patients with coagulation deficiency, we measured time curves of thrombin generation and fibrin clot formation (thromboelastography). Investigated were in study A: 10 patients treated with vitamin K antagonist and five healthy subjects; in study B: 30 patients undergoing cardiopulmonary bypass (CPB) surgery and infused with on average 2,000 ml crystalloids and colloids (no major bleeding); in study C: 58 patients undergoing major general surgery, and transfused with >5,000 ml crystalloids, colloids and red cell concentrates, who experienced major bleeding and were post-transfused with fresh frozen plasma. The treatment with vitamin K antagonist led to a progressive reduction in thrombin generation but not fibrin clot formation. In CPB patients, plasma factor levels post-surgery were 53–60% of normal. This was accompanied by moderate reduction in both haemostatic processes. In plasmas from patients undergoing major surgery, factor levels were 38–41% of normal, and these levels increased after plasma transfusion. Taking preset thresholds for normal thrombin generation and fibrin clot formation, at least one of these processes was low in 88–93% of the patients with (persistent) bleeding, but only in 40–53% of the patients without bleeding. In conclusion, the ability of thrombin generation and fibrin clot formation is independently reduced in acquired dilutional coagulopathy, while minimal levels of both are required for adequate haemostasis.
Keywords: Bleeding, dilutional coagulopathy, fibrin clot formation, surgery, thrombin generation